(3JHjjf GdMbGFb deG ajg ef JHjf eG GcJfR ef GdObGFbs - (3GdRjdYj, YKeGf Hf Ydj Hf eMLf, J (B743 (3g`s ((3eMeO Hf EHQGgje Hf CMeO GdNWjH HLGeY GdTjN CMeO YKeGf WGgQs)
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdTaYI hgj aj GddZI eCNhPI ef GdTaY hgh GdVe VO GdhJQ hefg TaGYI GdfHj Udi Gddg Ydjg hSde dCfg jVege HgG Edi GdaGFRjf jbGd (B: (3TaY GdQLd TaYG EPG cGf aQOG aUGQ dg KGf s
(3BNQgG (B:s
(3hSge ddCNJ dCH hSge ddCNJ dCe Ydi eG cGf (B( ) (3ef KeGfjI dCf CUdgG SJI JYhd Edi KeGfjI aEPG GSJhaJ GdCNJ fUjHgG hgh KdGKI Hbj NeSI hdh LYdJ cCfgG de Jcf dcGfJ ef SJI hHbj Sge ddYUHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 210s
(3eYLe GdeDdajf (B2 / 365s
(3cTa GdXfhf (B2 / 1515s
(3gOjI GdYGQajf (B1 / 655s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs